THE ROLE OF EDUCATION AND TRAINING IN THE DEVELOPMENT OF YOUNG ENTREPRENEURS - Albert Yansen; Miranu Triantoro; Purnama Sari (Adisam Publisher, 2024)
Education and training in the field of entrepreneurship are still considered to play an important role in strengthening the spirit of the young entrepreneur. The important role of education and training for the growth of entrepreneurial spirit. Various literature explains that the possession of entrepreneurial spirit is not merely due to an innate factor so that it automatically inherits in one's self, but can be formed and prepared through educational and training activities, so that one can become a tough entrepreneur. Therefore, to this day, various institutions of formal education have taught entrepreneurial education designed to equip young entrepreneurs so that they can become a successful entrepreneur. The research techniques that will be applied in this study include literature studies and library research, in which researchers use a range of literary sources to gather data for their investigations and employ a qualitative methodology due to the fact that the data generated by these sources takes the form of words or descriptions. The definition of young entrepreneurship, the function of education in fostering youth entrepreneurship, the function of training in fostering youth business development, and the connection between education and training in fostering young enterprise development are all covered in this study.